2004
DOI: 10.1080/09593332508618378
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Heavy Metals by Red Algae (Palmaria palmata)

Abstract: The biosorption of heavy metals from aqueous solutions was investigated, using a cheap and abundant dry biomass of red algae P. palmata. The Freundlich, Langmuir and Brunauer Emmer and Teller (BET) models were used to describe the uptake of lead (pb2+), copper (Cu2+), nickel (Ni2+), cadmium (Cd 2+) and zinc (Zn2+) on P. palmata. The good fits of the Langmuir and BET models to the experimental data reflected that the sorption on P. palmata was a multi-layer sorption, in which a Langmuir equation could be applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…Thermodynamic parameters (∆G 0 , ∆H 0 , ∆S 0 ) for M. spicatum were calculated from the variation of the thermodynamic equilibrium constant K 0 at various temperatures according to the following Eqs. (5) and (6):…”
Section: Biosorption Thermodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermodynamic parameters (∆G 0 , ∆H 0 , ∆S 0 ) for M. spicatum were calculated from the variation of the thermodynamic equilibrium constant K 0 at various temperatures according to the following Eqs. (5) and (6):…”
Section: Biosorption Thermodynamicsmentioning
confidence: 99%
“…In conventional practice, precipitation is the most common technology for metals removal, but chemical precipitation of heavy metals produces a large amount of sludge and is ineffective, especially when metals ion concentration in aqueous solution is as low as 100 mg/l [2]. Sorption is another well established technique for heavy metal removal, and activated carbon is the most widely used sorbent [3], However, the use of activated carbon can be expensive, so there has been considerable interest in the use of other sorbent materials, particularly biosorbents [4,5] such as marine algae [6], tobacco dust [7], wheat shell [8], stalk waste [9], soybean hull [10] and agricultural by-products [11]. Sorption by biomass is now recognized as an alternative method for the treatment of wastewaters containing heavy metals [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The phenomena of biosorption has been described in a wide range of living biomass like fungi [6], bacteria [7,8], yeast [9], moss [10], aquatic plants [11], and algae [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The investigations have shown that the biosorption of heavy metal cations by microorganisms is a rapid and reversible reaction and is not necessarily mediated by metabolic processes.…”
Section: Introductionmentioning
confidence: 99%
“…for the removal various heavy metal ions (Ni, Cu, Pb, Zn, Cd, and Al) from wastewater [19][20][21][22][23][24][25][26][27][28]. Biosorption potential of Spirogyra species was studied along with Lemna and Microcystis for removal of Pb, Cu, Cd, and Zn in single, bi-, tri-, and multimetallic mixture and differential pulse anodic stripping voltammetery was used for the measurements [22].…”
Section: Introductionmentioning
confidence: 99%
“…Seaweeds have a high bonding affinity with heavy metals [1,[14][15][16][17][18][19][20]. Since their cell walls have different functional groups (such as carboxyl, hydroxyl, phosphate or amine) that can bind to metal ions [21], they are much more efficient than active carbon and natural zeolites and, depending on the pH, these groups are either protonated or deprotonated [22,23].…”
Section: Introductionmentioning
confidence: 99%